2021
DOI: 10.1021/acs.jpcc.1c01006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Syngas to Higher Alcohols over Multifunctional Catalyst: The Role of Copper-Based Component and Catalytic Mechanism

Abstract: A multifunctional catalyst composed of CoMn and CuZnAlZr oxides can dramatically increase higher-alcohol selectivity. However, the role of Cu-based components and catalytic mechanism are still unclear. Herein, a series of multifunctional catalysts containing CoMn oxides and different Cu-based components were constructed to investigate the influence of a Cu component, and a link between methanol synthesis and higher-alcohol synthesis was established. It was found that the Cu-based components with different meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…One type of multifunctional catalyst contains a modified FTS component and methanol synthesis component such as CoMn|CuZnAlZr, CuCoAl|t-ZrO 2 , and CuCoAl|ZnO/ZrO 2 . ,,, Lin et al developed a multifunctional catalyst composed of CoMn and CuZnAlZr that offered 58.1% (CO 2 -free) oxygenate selectivity with more than 92 wt % being C 2+ OH at a CO conversion of 29.0% under 250 °C and H 2 /CO = 1 . The total selectivity of value-added chemicals including oxygenates and olefins reached up to 80.6 wt %.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…One type of multifunctional catalyst contains a modified FTS component and methanol synthesis component such as CoMn|CuZnAlZr, CuCoAl|t-ZrO 2 , and CuCoAl|ZnO/ZrO 2 . ,,, Lin et al developed a multifunctional catalyst composed of CoMn and CuZnAlZr that offered 58.1% (CO 2 -free) oxygenate selectivity with more than 92 wt % being C 2+ OH at a CO conversion of 29.0% under 250 °C and H 2 /CO = 1 . The total selectivity of value-added chemicals including oxygenates and olefins reached up to 80.6 wt %.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…Previous studies have suggested that the insertion of CO/CH x O* species into alkyl species () is the key step for HA synthesis. 36 The CO 2 hydrogenation performance of sole CH 3 OH/CO synthesis catalysts was also studied and the results are shown in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
“…25 Therefore, the rational introduction of a promoting component for CO/CH x O synthesis into the C–C coupling network is an effective strategy for HAS. 25,28,32,33,36 Given the above analysis, a plausible reaction mechanism for the tandem catalysis of HAS is proposed, as shown in Scheme 1. Over the sole primary KCFZ catalyst, HA follows a tandem mechanism of rWGSR and coupling of CH x and CO* via an aldehyde intermediate ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As dual active sites are required for alcohols formation from syngas conversion, HAS catalysts always contain at least binary metals, such as Cu–Fe, 10,17,18 Cu–Co, 19,20 and Rh–Mo. 21 In addition, relay catalysis 22–24 and multifunctional catalysis 25,26 have been proposed to enhance alcohols formation. Importantly, Mo-based catalysts exhibit high stability with sulfur resistance for the HAS reaction.…”
Section: Introductionmentioning
confidence: 99%